The influence of tantalum oxide nanoparticle on thermal conductivity and tear strength after addition on maxillofacial silicone [version 2; peer review: 1 approved, 1 approved with reservations] - Ali Mousa, saif; Abdullah, Zainab Saleh (F1000 research, 2025)
Background Maxillofacial prosthetic materials exhibit a range of qualities that vary considerably, including the hardness and stiffness of alloys and polymers, as well as the flexibility of elastomers and soft polymers. Silicone elastomers are the primary materials employed for maxillofacial prostheses due to their physical properties, which allow for adaptation to the movement of soft tissue. They also exhibit exceptional tensile and tear strength across a broad temperature range. Silicone elastomers can be classified according to the vulcanization process: High-temperature vulcanization (HTV) silicones, and Room temperature vulcanization (RTV) silicones. The addition of nanoparticle enhances thermal and tear strength of maxillofacial silicon. This study estimates the influence of addition tantalum oxide nanoparticle on thermal conductivity and tear strength after addition on maxillofacial silicone. Method Tantalum oxide nanoparticles were added into VST-50F platinum silicone elastomer at two weight percentages: 1wt% and 1.5wt%. 60 specimens were prepared and classified into two groups: one control group for each property and two experimental groups. All collected data underwent statistical analysis by one-way ANOVA and Bonferroni's multiple comparison test, with significance set at p < 0.05. The Shapiro-Wilk test and Bartlett's test were employed to assess the normality and homogeneity of the data, respectively. Result The one-way ANOVA test found a very significant difference between all groups, while Bonferroni's test revealed a highly significant difference between the control and experimental groups. Thermal conductivity test found no significant difference between the 1wt% and 1.5wt% groups, however the tear strength test was highly significant. Conclusions The addition tantalum oxide nano particles improve tear strength and thermal conductivity.